2021
DOI: 10.2147/pgpm.s335555
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variant of PP2A Subunit Gene Confers an Increased Risk of Primary Liver Cancer in Chinese

Abstract: Background: Protein phosphatase 2A (PP2A, a serine/threonine phosphatase) is frequently inactivated in many types of cancer, including primary liver cancer (PLC). Genetic variations in PP2A subunits have been reported to be associated with the risk of many types of cancer but rarely in PLC. This study aims to assess the association between functional polymorphisms of PP2A subunit genes and the risk of PLC in Chinese. Methods: In a case-control study with a total of 541 PLC patients and 547 controls in Guangxi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“… 20 , 21 A pond/ditch was defined as a water storage place, approximately 5–6 m in width, 100 m in length, and 1–2 m in depth, usually located close to residential areas. 6 Participants who had used water from ponds/ditches as the source of drinking water for 20 years or more were defined as drinkers of pond/ditch water. 6 This study was approved by the Medical Ethics Committee of Guangxi Medical University (GXMU-20160303-9), and the study was conducted in accordance with the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“… 20 , 21 A pond/ditch was defined as a water storage place, approximately 5–6 m in width, 100 m in length, and 1–2 m in depth, usually located close to residential areas. 6 Participants who had used water from ponds/ditches as the source of drinking water for 20 years or more were defined as drinkers of pond/ditch water. 6 This study was approved by the Medical Ethics Committee of Guangxi Medical University (GXMU-20160303-9), and the study was conducted in accordance with the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
“… 6 Participants who had used water from ponds/ditches as the source of drinking water for 20 years or more were defined as drinkers of pond/ditch water. 6 This study was approved by the Medical Ethics Committee of Guangxi Medical University (GXMU-20160303-9), and the study was conducted in accordance with the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A survey of 134 lakes in New Zealand found that the highest concentration of microcystins was 6.4 μg/L [ 20 ]. In 29 pond/ditch drinking water samples collected in Nanning District, Guangxi, China, the average MC-LR concentration was 0.5 μg/L [ 21 ]. The microcystin content was 13.38 μg/L, and the highest concentration was 35.8 μg/L in Lake Taihu of China after the collapse of cyanobacterial blooms, which greatly exceeded the WHO standard of 1 μg/L [ 22 ].…”
Section: Introductionmentioning
confidence: 99%